Hemodynamic Profile of Patients with ESKD Referred to Heart Failure Department of Rajaie Heart Center, A Data from Right Heart Catheterization Registry (Iranian Journal of Kidney Diseases, 2022)
Introduction. Cardiovascular disorders are the leading cause of mortality and morbidity in patients with end-stage kidney disease (ESKD). We aimed to describe different patterns of cardiovascular abnormalities, the hemodynamics and the outcomes of ESKD patients referred to a tertiary center for heart failure programs, in detail. Methods. In this cohort, all ESKD patients who were referred by nephrologists for cardiovascular consultation and scheduled for right heart catheterization between July 2009 to October 2021, were assessed. The outcome of the selected patients in terms of all-cause mortality or successful kidney transplantation was followed up until January 2022. Results. A total of 73 patients (54.7% male) were selected. With the exception of four patients who had a specific cardiovascular disease, the remainder were referred due to a low left ventricular ejection fraction or pulmonary hypertension in order to determine the potential for kidney transplantation. Most of the patients (63%) were categorized as heart failure with reduced ejection fraction (HFREF). More than 87% of study population had pulmonary hypertension (PH). Post capillary PH (isolated or combined) was the most common type of PH (81%). The median interquartile range (IQR) of time to kidney transplantation or all-cause mortality was 1 (0.5 to 2) year. Twenty-five (36.2%) patients received a successful kidney transplant. The all-cause mortality rate was 28.8%. Older age, lower left ventricular ejection fraction (LVEF) and presence of pericardial effusion were independent predictors of all-cause mortality in multivariate analysis. Conclusion. ESKD patients with HFREF and/or pulmonary hypertension will have remarkable improvement in terms of their cardiac performance parameters following kidney transplantation.  DOI: 10.52547/ijkd.7105